The Behaviour Of Malaysian Stock Market Investors - Abdullah, Nurliyana Thoh (2005)
This research comes from a behavioral viewpoint on corporate finance and tries to explain the behavior of investors from a psychological approach, specifically by using prospect theory. The behavior of investors is captured through trading volume and the reaction is based on earnings surprise during earnings announcements. It is hypothesized that trading volume and earnings surprise is positively correlated, thus, predicting that investors would trade more during positive earnings surprises compared to negative earnings surprises.